The Formation of Electronic Contracts in Chinese E-Commerce: Electronic Offers, Electronic Acceptances, and Procedural Regulation - Shen, Zeran (International Journal of Social Sciences and Public Administration, 2026)
Electronic contracts have become a common form of contract formation in e-commerce transactions, but their electronic and platform-based nature has made the distinction between offers and acceptances more complex. This article focuses on the formation of electronic contracts in Chinese e-commerce, with electronic offers and electronic acceptances as the main line of analysis. Under the framework of the Civil Code of the People’s Republic of China, the E-Commerce Law of the People’s Republic of China, and the Electronic Signature Law of the People’s Republic of China, it examines the legal nature of product page information, the effect of order submission, the role of payment, and the regulation of standard terms. It argues that electronic contract formation should be assessed within the overall transaction process rather than by isolated procedural steps. On this basis, the article proposes to refine the rules on webpage information, clarify the consequences of order submission, restrict the abuse of standard terms, and strengthen platform governance, so as to balance transaction efficiency, consumer reliance, and the legitimate interests of e-commerce operators.